1988
DOI: 10.1103/physrevb.38.3564
|View full text |Cite
|
Sign up to set email alerts
|

Electronic-structure method for general space-filling cell potentials

Abstract: It is shown that the scattering matrix in the form describing multiple-scattering processes for collections of muIIln-tin (MT) potentials is rigorously valid for nonoverlapping potentials of arbitrary shape. In particular, the near-field corrections (NFC's) ostensibly arising in the latter case are shown to vanish identically. It follows that the well-known method of Korringa and of Kohn and Rostoker for calculating electronic structure is valid for non-MT potentials. Model calculations illustrating directly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Growing interest in the electronic structure of complicated materials with more open structures that are not well described by muffin-tin potentials, has led to the development of full-potential bandstructure techniques. For example, full-potential KKR bandstructure methods can be found by Williams and van Morgan (1974), Brown andCiftan (1983, 1986), Gonis et al (1988, , Butler and Nesbet (1990) and Butler et al (1992). Full-potential linearized-muffin-tin-orbital (LMTO) techniques have been introduced by Weyrich (1988), Methfessel (1988) and Methfessel et al (1989) and fullpotential linearized-augmented-plane-wave (LAPW) bandstructure calculations have been performed by Wimmer et al (1981).…”
Section: Full-potential Photoemission Theorymentioning
confidence: 99%
“…Growing interest in the electronic structure of complicated materials with more open structures that are not well described by muffin-tin potentials, has led to the development of full-potential bandstructure techniques. For example, full-potential KKR bandstructure methods can be found by Williams and van Morgan (1974), Brown andCiftan (1983, 1986), Gonis et al (1988, , Butler and Nesbet (1990) and Butler et al (1992). Full-potential linearized-muffin-tin-orbital (LMTO) techniques have been introduced by Weyrich (1988), Methfessel (1988) and Methfessel et al (1989) and fullpotential linearized-augmented-plane-wave (LAPW) bandstructure calculations have been performed by Wimmer et al (1981).…”
Section: Full-potential Photoemission Theorymentioning
confidence: 99%
“…In the first term of (34b), rm E 9m and rb E uO. So, rm + Rmo < rh (24), and the two-center GF expansion (25) may be used. In the second term of (34b), r, E 9 , and rL E a,.…”
Section: Non-mt Secular Equationmentioning
confidence: 99%
“…Additionally, Keister [lo] has demonstrated that, in practice, the divergent series may not lead to some troubles, because of their asymptotic, semiconvergent nature. On the other hand, Gonis et al [13,24], Zhang et al [27,28], and Molenaar [19] have given reasons for the difficulties with the summations of divergent series virtually not to exist. To draw such a conclusion, they put forward a procedure by which the origins of cells should be shifted.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recently a great deal of work has been directed at the generalization of the KKR method to space-filling cells. Much of this work has established [25][26][27][28][29][30][31][32] that, as far as the band structure of a material is concerned, multiple-scattering theory (MST) assumes identical forms in both the case of MT and the case of space-filling cells. In fact, in all its manifestations, MST retains one of its most advantageous features, namely the separability of the structural aspects from the potential aspects of a scattering assembly.…”
Section: Introductionmentioning
confidence: 99%